Buddhist Principles in Urban Livability Assessment: A Thematic Analysis of Integration Approaches in Contemporary Research (2015-2024) - Kiatanantha Lounkaew (Journal of International Buddhist Studies)
This paper explores the integration of Buddhist philosophies into urban livability assessment frameworks through analysis of literature from 2015-2024. While traditional measurements rely primarily on quantitative metrics, Buddhist principles offer broader perspectives for addressing urbanization challenges, climate change, and inequality. Our methodology employed systematic literature review, thematic content analysis, and comparison of implementation patterns across urban settings. We analyzed academic texts, policy documents, and case studies on Buddhist concepts in urban contexts, focusing on principles like interconnectedness, mindfulness, ethical conduct, and the middle way. The research identifies implementation challenges and opportunities across regions, with traditionally Buddhist areas showing higher adoption rates, though principles remain universally applicable. Cities with strong institutional support demonstrate higher implementation success. Our framework links Buddhist values to specific urban applications, evaluation criteria, implementation challenges, and benefits. Interconnectedness (paticca samuppada) informs neighborhood designs that reduce travel time and foster social interactions. Mindfulness (sati) creates spaces that reduce stress, while compassion (karuna) manifests in inclusive housing policies that decrease homelessness and improve public health. Environmental assessment components align with Buddhist teachings on stewardship and human-nature interconnectedness. This research bridges ancient insights with contemporary urban challenges, offering practical guidance for urban planners seeking to create more sustainable, equitable, and spiritually enriching urban environments.